Innovation in Education: A winning transformation tool in the era of the new ICT Revolution - SEKE, MBOUNGOU MOUYABI (IJRDO- Journal of Educational Research, 2017)
ICT-based technologies are the drivers of the current paradigm, which, the authordiscussed in previous contributions, is still at an early stage of diffusion, particularlyfor emerging countries. Building from historical evidence, the author argues thatcatching up of innovative education critically depends on the ability of educators tomaster the technology behind the dominant techno-economic paradigm and foreducational institutions to adapt on the shift of the current paradigm. The author thendiscusses threats and opportunities related to a possible ICT-based development path.